The Qatar Pediatric Emergency Medicine International Conference – Knowledge Translation Successes and Challenges - Barbara Blackie (18505041) (2024)
Background The Qatar Pediatric Emergency Medicine (Q-PEM) annual conference (Figure 1) started in 2017 with its first iteration provided as a face-to-face event. The conference goals are to provide accessible, evidence-based updates on the care of acutely unwell or injured patients for an interprofessional audience. At its inception, there was no equivalent event in Qatar, with both injury and illness as a focus. The conference, because of COVID-19, has evolved into an online conference, to reach a wider audience in the region and beyond, and to invite international speakers. Methods The scientific committee selects topics based on the self-identification of knowledge gaps by participants, from leadership in various Pediatric Emergency Centers and Departments at Hamad Medical Corporation and Sidra Medicine, and from literature searches on the latest evidence in PEM. Topics are selected with a view to help ‘translate knowledge to practice’ for participants, allowing them to incorporate best evidence into their decision making. This process is aided by a program that includes a large amount of Question and Answer time, case-based studies, and polling of the audience to enhance knowledge acquisition. Findings This annual conference, accredited for Continuing Professional Development (CPD) credits, has become increasingly popular and surpassed 4,400 participants since 2017 (Table 1). There are 20+ CPD hours each year, with 50+ topics. The online platform enables participants access to recorded sessions for several months post conference. A follow up survey is planned to identify if and how the participants are changing and practice based on the conference. Conclusion QPEM, about to have its 8th annual conference is an increasingly popular venue for the dissemination of high-quality evidence in the practice of PEM in Qatar and the region and is the product of a strong collaboration between Sidra Medicine and Hamad Medical Corporation.